Junctophilin-1 is a modifier gene of GDAP1-related Charcot–Marie–Tooth disease - Pla-Martín, David; Calpena, Eduardo; Lupo, Vincenzo; Márquez, Celedonio; Rivas, Eloy; Sivera, Rafael; Sevilla, Teresa; Palau, Francesc; Espinós, Carmen (Human molecular genetics, 2015)
Mutations in the GDAP1 gene cause different forms of Charcot-Marie-Tooth (CMT) disease, and the primary clinical expression of this disease is markedly variable in the dominant inheritance form (CMT type 2K; CMT2K), in which carriers of the GDAP1 p.R120W mutation can display a wide range of clinical severity. We investigated the JPH1 gene as a genetic modifier of clinical expression variability because junctophilin-1 (JPH1) is a good positional and functional candidate. We demonstrated that the JPH1-GDAP1 cluster forms a paralogon and is conserved in vertebrates. Moreover, both proteins play a role in Ca(2+) homeostasis, and we demonstrated that JPH1 is able to restore the store-operated Ca(2+) entry (SOCE) activity in GDAP1-silenced cells. After the mutational screening of JPH1 in a series of 24 CMT2K subjects who harbour the GDAP1 p.R120W mutation, we characterized the JPH1 p.R213P mutation in one patient with a more severe clinical picture. JPH1(p.R213P) cannot rescue the SOCE response in GDAP1-silenced cells. We observed that JPH1 colocalizes with STIM1, which is the activator of SOCE, in endoplasmic reticulum-plasma membrane puncta structures during Ca(2+) release in a GDAP1-dependent manner. However, when GDAP1(p.R120W) is expressed, JPH1 seems to be retained in mitochondria. We also established that the combination of GDAP1(p.R120W) and JPH1(p.R213P) dramatically reduces SOCE activity, mimicking the effect observed in GDAP1 knock-down cells. In summary, we conclude that JPH1 and GDAP1 share a common pathway and depend on each other; therefore, JPH1 can contribute to the phenotypical consequences of GDAP1 mutations.